115 Minimally Invasive Versus Open Lumbar Spinal Fusion: A Matched Study Investigating Patient-Reported and Surgical Outcomes. (1st April 2022) - Mooney, James Henry; Michalopoulos, Giorgos; Alvi, Mohammed; Zeitouni, David; Chan, Andrew K.; Mummaneni, Praveen V.; Bisson, Erica F.; Haid, Regis W.; Knightly, John J.; Devin, Clinton J.; Pennicooke, Brenton H.; Asher, Anthony L.; et al.
Abstract : INTRODUCTION: With the expanding indications for and increasing popularity of minimally invasive spine surgery (MIS) for lumbar spinal fusion, large-scale analysis of patient outcomes after MIS approaches compared to traditional open procedures is warranted. METHODS: Patients undergoing MIS and open lumbar fusion were matched at a 1:2 ratio on 33 baseline variables to create two highly homogeneous groups. Primary endpoints of interest were overall satisfaction and a decrease in Oswestry Disability Index (ODI) at 3 months postoperatively. Satisfaction was defined as score 1-2 in the North American Spine Association index; minimal clinically important disease (MCID) for ODI was defined as = 30% decrease from baseline. Secondary endpoints were satisfaction and decrease in ODI at 12 months, length of stay (LOS), operative time, and incidental durotomy rate. RESULTS: The MIS and open groups consisted of 1, 483 and 2, 966 patients, respectively. MIS fusion patients had a higher odds of satisfaction compared to open surgery at 3 months (OR = 1.4, p = 0.004), while maintaining non-inferior odds of satisfaction at 12 months (OR = 1.04, p = 0.67). Lumbar stenosis, single-level fusion, predominant back pain, higher ASA grade, and absence of spondylolisthesis were associated with higher odds of satisfaction with MIS compared to open surgery. Patients in the MIS group had slightly lower ODI scores at 3 months (mean difference=1.61, p = 0.006; MCID OR = 1.14, p = 0.0495), and 12 months (mean difference=2.35, p < 0.001; MCID OR = 1.29, p < 0.001). The groups did not differ in terms of operative time and incidental durotomy rate; however, LOS was shorter for the MIS group. CONCLUSION: These results demonstrate that MIS fusion is associated with higher odds of satisfaction and, possibly, a greater decrease in ODI than open fusion at 3 months postoperatively while maintaining a greater ODI improvement and performing non-inferiorly to open in regards to satisfaction at 12 months.